Sistem Monitoring Pasien Isolasi Mandiri Covid-19 Melalui Website Cayenne Berbasis Nodemcu ESP8266 - Daniel Rudiaman Sijabat; Zulfan Hindharaka Zudhan (J-INTECH ( Journal of Information and Technology), 2022)
In 2019, a new disease called Coronavirus 2019 (COVID19) emerged. The clinical symptoms of people affected by the COVID19 virus are mostly difficulty in breathing and results from X-rays showing significant infiltrating pneumonia in both lungs. In cases of severe pneumonia in adolescent or adult patients, blood oxygen saturation levels can decrease to less than 90% and are followed by changes in heart rate with symptoms of tachycardia or bradycardia. The high number of COVID-19 cases has resulted in fewer hospital facilities, so patients with mild symptoms are advised to self-isolate. The oxygen saturation levels and heart rate of patients who carry out independent isolation need to be monitored. Based on the problems above, this research was conducted and aims to develop an independent patient isolation monitoring system so that the patient's condition can be monitored remotely in real time. The monitoring system was developed using the NodeMCU ESP8266 and using the MAX30100 sensor to obtain oxygen saturation data and patient heart rate data. The readings from the sensors are then sent to the Cayenne Website so that the patient's oxygen saturation and heart rate information can be read in real time by the doctor and also the patient's family via a browser.